2020
DOI: 10.3390/plants9030291
|View full text |Cite
|
Sign up to set email alerts
|

Excess Copper-Induced Alterations of Protein Profiles and Related Physiological Parameters in Citrus Leaves

Abstract: This present study examined excess copper (Cu) effects on seedling growth, leaf Cu concentration, gas exchange, and protein profiles identified by a two-dimensional electrophoresis (2-DE) based mass spectrometry (MS) approach after Citrus sinensis and Citrus grandis seedlings were treated for six months with 0.5 (control), 200, 300, or 400 μM CuCl2. Forty-one and 37 differentially abundant protein (DAP) spots were identified in Cu-treated C. grandis and C. sinensis leaves, respectively, including some novel DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 87 publications
(126 reference statements)
1
14
0
Order By: Relevance
“…Superoxide dismutase (SOD) can rapidly dismutase superoxide anion into H 2 O 2 and O 2 . Our findings that Fe/Mn-SOD and Cu/Zn-SOD ( CSD ) were downregulated and upregulated in LCGSEC, respectively is in agreement with the reports that Fe-SOD abundance was reduced and CSD abundance was elevated in Cu-sufficient Arabidopsis leaves [ 58 ] and that Cu-toxicity increased CSD abundance, but had no influence on Fe-SOD abundance in C. grandis leaves [ 20 ]. Plants that suppress Fe-SOD and induce CSD under Cu-toxicity can keep superoxide anion scavenging and prevent the Cu-toxic effect on photosynthesis by buffering Cu concentration [ 11 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Superoxide dismutase (SOD) can rapidly dismutase superoxide anion into H 2 O 2 and O 2 . Our findings that Fe/Mn-SOD and Cu/Zn-SOD ( CSD ) were downregulated and upregulated in LCGSEC, respectively is in agreement with the reports that Fe-SOD abundance was reduced and CSD abundance was elevated in Cu-sufficient Arabidopsis leaves [ 58 ] and that Cu-toxicity increased CSD abundance, but had no influence on Fe-SOD abundance in C. grandis leaves [ 20 ]. Plants that suppress Fe-SOD and induce CSD under Cu-toxicity can keep superoxide anion scavenging and prevent the Cu-toxic effect on photosynthesis by buffering Cu concentration [ 11 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 92%
“…‘Shatian’ pummelo [ Citrus grandis ) (L.) Osbeck] is one of the main rootstocks of pummelo. Recent work from our laboratory indicated that ‘Shatian’ pummelo had a higher tolerance to Cu-toxicity and was an ideal material to investigate the adaptive mechanism of Cu-toxicity [ 2 , 20 ]. Herein, 400 μM Cu was chosen as the Cu-toxicity treatment because it led to significant but not too severe alterations of biomass, nutrient uptake, photosynthesis and related parameters in C. grandis seedlings [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, owing to various anthropogenic activities, this HM has gained particular attention among plant stress physiologists due to its dual nature in the plant system: essential as well as toxic at an optimum and high level respectively [9,10]. An excess of Cu concentration in plant tissues induces oxidative stress via enhanced biosynthesis of various reactive oxygen species (ROS), resulting in damage to photosystem pigment proteins, DNA, RNA, lipids, enzymes, altered thylakoid membranes composition, decreased chlorophyll and mineral nutrient contents and hampered meristems development [11][12][13][14][15]. Hence, given its dual nature (essential as well as toxic), this HM could involve complex mechanisms of uptake, transport, sequestration and detoxification inside the plant tissues at the cellular level.…”
Section: Introductionmentioning
confidence: 99%